Green Housekeeping Implementation Challenges and Sustainability Strategies in Surabaya Hotels Qualitatively Explored - Riris Yuniarsih (Journal of Tourism Economics and Policy, 2026)
The hospitality industry is increasingly required to implement sustainable operational practices to reduce environmental impacts. This study aims to explore the implementation of green housekeeping in a hotel in Surabaya by identifying the practices applied, the challenges encountered, and the strategies adopted to sustain successful implementation. This study employed a descriptive qualitative approach using in-depth interviews, observations, and documentation involving the Executive Housekeeper, Housekeeping Supervisor, and Room Attendant. Data were analyzed through data reduction, data display, and conclusion drawing, while data credibility was ensured through source and method triangulation. The findings reveal that green housekeeping has been integrated into daily hotel operations through linen reuse programs, efficient water and energy consumption, waste segregation, environmentally friendly cleaning materials, and guest environmental awareness initiatives. Nevertheless, its implementation continues to face challenges, including diverse guest preferences, high operational workloads, varying levels of employees' environmental awareness, and limitations in facilities and technology investment. To address these challenges, the hotel implements continuous employee training, resource monitoring and evaluation, guest education, cross-departmental coordination, and gradual technological modernization. The study demonstrates that successful green housekeeping implementation depends on the synergy among management commitment, human resources, operational processes, technological support, and stakeholder participation. These findings contribute to the existing body of knowledge on operational-level green housekeeping implementation and provide practical guidance for hotel managers in developing more effective sustainability strategies.